Globalización y comunidad de vecindad. Notas para el planteamiento de un concepto - Pérez Sáinz, Juan Pablo (2006)
“Globalization” suggests ideas like compression of the world, the development of a planetary conscience or the negation of space by time. In this sense, it is possible to think about a homogenization process on a world-wide scale; nevertheless, the empirical evidence indicates the contrary. This article tries to precise the term. In first place, it deals with the relation between globalization and territoriality. Then, it shows different local manifestations in order to raise the concept of neighbourhood community, a pertinent concept for such Latin American realities, whose central characteristic is coincidence of life spaces and work. The article concludes with reflections on the analytical challenges that the term raises.